Unge lovbrytere : Forsømte eller forbryterske? - Ericsson, Kjersti (Nordisk Tidsskrift for Kriminalvidenskab, 2000)
Are juvenile delinquents to be regarded as neglected children or as criminals? Should they be taken care of by child welfare, or should they go to court and be punished for their acts? In post-war Norway, there have been several ideological shifts on this topic. ln the forties and early fifties, the climate was optimistic. There was a strong belief in treatment, care, and education. With rising juvenile delinquency in the late fifties and sixties, the optimism waned. The solution to the problem was increasingly sought in criminal justice. The seventies saw a new turn of the ideological tides. The imprisonment of children was now seen as a moral outrage. After a while, this issue crystallized into a debate on whether the age of criminal liability should be raised from fourteen to fifteen years. This debate marked the starting point for transferring the responsibility for youth delinquency from the criminal justice system back into the hands of child welfare and health - and social services. Some lasting dilemmas have accompanied these shifts: Is it possible to smoothly combine measures "in the best interest of the child" with effective crime control? When individual preventive considerations in criminal justice gain such force that they conflict strongly with the demand for proportionality between offence and punishment, they become indefensible. And when treatment has to be administered through extensive use of coercion, doubts arise. These dilemmas remain unsolved.